Komparasi Efektivitas Daun Salam (Syzygium Polyanthum) dan Jahe (Zingiber Officinale) terhadap Kadar Gula Darah pada Pasien Diabetes Melitus Tipe 2 - Novita Dewi; Supriyadi Supriyadi; Errick Endra Cita (Jurnal Akademika Baiturrahim Jambi, 2022)
Diabetes Mellitus Type 2 (DMT2) is a major problem in health, the number of deaths, the high cost of care. DMT2 has an increase in glucose (hyperglycemic) due to insulin metabolism problems in the body. Giving bay leaf powder and ginger can reduce blood glucose in patients with T2DM. The aim of the study was to compare the effectiveness of bay leaves and ginger on blood sugar levels in T2DM patients. The population of all DMT2 patients was 30 people, a sample of 23 DMT2 patients, aged 35-70 years, all DMT2 patients who underwent treatment for 1 week, with a dose of 1 capsule twice per day as much as 1000 mg, analysis using paired test and T-Test. The results of the T-Test value study showed the effect of ginger powder consumption on blood glucose levels in T2DM patients. There is an effect of consumption of bay leaf powder on blood glucose levels in patients with T2DM. There was no significant difference between the consumption of ginger powder and bay leaf on blood glucose levels in patients with T2DM. The recommendation for further research is to conduct further research, prioritizing digging in more detail about confounding factors and observing these confounding factors.